Practical static analysis of context leaks in Android applications. (7th November 2018) - Toffalini, Flavio; Sun, Jun; Ochoa, Martín
Summary: Android native applications, written in Java and distributed in APK format, are widely used in mobile devices. Their specific pattern of use lets the operating system control the creation and destruction of resources, such as activities and services (contexts). Programmers are not supposed to interfere with such life cycle events. Otherwise, contexts might be leaked, ie, they will never be deallocated from memory, or be deallocated late, leading to memory exhaustion and frozen applications. In practice, it is easy to write incorrect code, which hinders garbage collection of contexts and leads to context leakages. In this work, we present a novel static analysis method that finds context leaks in Android code. We apply this analysis to APKs translated into Java bytecode. We provide a formal analysis of our algorithms and suggest further research directions for improving precision by combining different approaches. We discuss the results of a large number of experiments with our analysis, which reveal context leaks in many widely used applications from the Android marketplace. This shows the practical usefulness of our technique and its superiority w.r.t. the well‐known Lint and Infer static analysis tools. We estimate the amount of memory saved by the collection of the leaks found and explain, experimentally, where programmers often go wrong and limitations of our tool. Such lessons could be used for designing of a sound or more powerful static analysis tool. This work can be considered as a practical application of software analysis techniques to solve practical problems.